A multi-functional reagent suitable for 1-step rapid DNA intercalation fluorescence-based screening of total bacteria in drinking water. (February 2023) - Lim, Hyun Jeong; Hong, Seungwon; Jin, Hyowon; Chua, Beelee; Son, Ahjeong
Abstract: The prerequisites for rapid screening of total bacteria in drinking water are low detection limit and convenience. Inspired by commercial adenosine 5′-triphosphate (ATP) based total bacterial detection kits, we pursued likewise convenience but with much lower detection limit. Existing intercalation fluorescence-based techniques employ multiple reagents to permeate the cell membrane and intercalate dye into the DNA in discrete sequential steps. A simple multi-functional reagent is proposed to do the same within one step. Surfactants (TritonX and SDS), and intercalating dyes (SYBR green, SYBR gold) were examined for their mutual compatibility and augmented with EDTA. Evaluation was performed with Gram negative Escherichia coli K12 ( E. coli K12) and Gram positive Bacillus subtilis ( B. subtilis ) at serial dilution ratios from 10 −6 to 10 −2 . Comparison was made with absorbance (600 nm) measurements and a commercial ATP kit. Using charge integrated photodetection, the proposed 1-step reagent achieved an LOD (1.00 × 10 −6, B. subtilis ) that is two orders of magnitude lower than that of ATP kit (LOD = 1.06× 10 −4 ). This means it could detect minute quantity of total bacteria that is otherwise undetected by the ATP kit. Graphical abstract: Image 1 Highlights: Rapid and convenient total bacterial detection using multi-functional 1-step reagent. Permeate bacterial cell membrane and intercalate DNA with fluorescent dye with one reagent. Simple formulation using existing surfactants and intercalating dyes. High performance detection with LOD at 1 × 10 −6 serial dilution ratio. Detect minute quantity of total bacteria otherwise undetected by ATP kits (LOD 1 × 10 −4 ).